Knowledge, Perceptions and Use of Electronic Cigarettes Among Health Professionals: Knowledge, Perceptions and Use of Electronic Cigarettes - Shahbaz , Ferheen; Waqas Ahmad, Hafiz; Ahmad, Saeed; Abid, Isma; Abdisamad Mohamad, Abdurahman; Ansa, Nimra; Haider, Naveed; Saleem, Javeria; Tahir, Naveed; Shahbaz, Mehreen (Pakistan Journal of Health Sciences, 2023)
In the developing era we are facing increasing prevalence of tobacco use and rapid increase of e-cigarette. Health professional are no longer found to abstain from e-cigarettes. The growing interest of vaping in our society leads to us a debate that e-cigarette are the tools to refrain from smoking or these are provoking people towards more smoking. Objectives: to evaluate the knowledge and concepts of e-cigarettes. And how the health professional perceive the use of vaping over smoking tobacco? What are the attitudes of vaping in health care professional? Methods: A descriptive cross-sectional study based on questionnaire filling survey, filled by 350 health professionals working in Jinnah hospital Lahore. The questionnaire compromises on four parts; demographic data, knowledge and attitudes toward vaping behavior, interest and trend of e-cigarettes, and perception of harms and health related risks. Results: data collected from 350 individuals. Average age of health professionals included in study was 30.6(2.60). A large percentage was found for former smokers 22% and current smokers 39%. Vape users also found in increasing percentages.so far the mass media roles were evaluated in smoking cessations. A cumulative percentage of 42%, electronic cigarettes were supported by the health professionals. Despite of good knowledge most of the professional had opinion in support of e-cigarettes upto 64% and the results were significantly proven by p-value 0.03. the knowledge and attitudes that e-cigarettes is less harmful than combustible tobacco smoking with and cumulative percent of 76% . Conclusion: health care professionals working in Jinnah hospital Lahore have favorable attitudes towards vaping or e-cigarettes perceived thought of vaping is less harmful than tobacco smoking is also highlighted. The need of the hour is to highlight the health related problems by e-cigarettes in our society to control the behaviors of population towards e-cigarettes.